The Role of TLR2 and Bacterial Lipoprotein in Enhancing Airway Inflammation and Immunity - Lugade, Amit A.; Bogner, Paul N.; Murphy, Timothy F.; Thanavala, Yasmin (Frontiers in Immunology, 2011)
Non-typeable Haemophilus influenzae (NTHI) colonizes the lower respiratory tract of patients with chronic obstructive pulmonary disease (COPD) and also causes exacerbations of the disease. The 16-kDa lipoprotein P6 has been widely studied as a potential vaccine antigen due to its highly conserved expression amongst NTHI strains. Although P6 is known to induce potent inflammatory responses, its role in the pathogenesis of NTHI infection in vivo has not been examined. Additionally, the presence of an amino-terminal lipid motif on P6 serves to activate host TLR2 signaling. The role of host Toll-like receptor 2 (TLR2) and NTHI expression of the lipoprotein P6 on the induction of airway inflammation and generation of adaptive immune responses following chronic NTHI stimulation was evaluated with TLR2-deficient mice and a P6-deficient NTHI strain. Absence of either host TLR2 or bacterial P6 resulted in diminished levels of immune cell infiltration within lungs of mice exposed to NTHI. Pro-inflammatory cytokine secretion was also reduced in lungs that did not express TLR2 or were exposed to NTHI devoid of P6. Induction of specific antibodies to P6 was severely limited in TLR2-deficient mice. Although mice exposed to the P6-deficient NTHI strain were capable of generating antibodies to other surface antigens of NTHI, these levels were lower compared to those observed in mice exposed to P6-expressing NTHI. Therefore, cognate interaction between host TLR2 and bacterial P6 serves to enhance lung inflammation and elicit robust adaptive immune responses during NTHI exposure. Strategies to limit NTHI inflammation while simultaneously promoting robust immune responses may benefit from targeting the TLR2:P6 signaling axis.